Extracellular vesicles as next-generation therapeutics and biomarkers in amyloidosis: a new frontier - Phan, Thanh Huyen; Reed, Joanne H. (Frontiers in Biomaterials Science, 2024)
Nanoparticles hold a great potential for therapeutic targeting due to their ability to improve the stability of encapsulated cargo and promote the transport of cargo across membranes to reach to the target site. Most commercially available nanomedicines are simple synthetic liposomes, however, there are numerous side effects due to their off-target delivery and rapid clearance from the bloodstream. Recently, attention has moved toward extracellular vesicles (EVs) -lipid bilayer enclosed particles released by cells (size ranging from 30 nm to 10,000 nm in diameter). EVs carry and transport lipids, proteins, and nucleic acids from their parental cells to recipient cells, hence they play a key role in intercellular communication. The ability of EVs to cross biological barriers including the blood brain barrier has generated significant attention to explore them as potential biomarkers and natural drug delivery vehicles for various therapeutics and small molecules. EVs have also been implicated in disease pathogenesis by transmitting pathogenic proteins between cells, making them promising biomarkers for disease diagnosis and monitoring. In this review, we will focus on the potential and challenges of EVs as biomarkers, drug delivery vehicles and nextgeneration therapeutics. Finally, we will explore misfolded protein disorders, amyloidosis, as a case study for how EVs may contribute to disease pathology and how EVs could be applied in the clinic as diagnostic and prognostic biomarkers of amyloid diseases.